38. HISTOLOGICAL AND BIOCHEMICAL CHANGES FOLLOWING ISONIAZID INDUCED HEPATOTOXICITY IN YOUNG AND OLD FISCHER 344 RATS. (February 2015) - Mach, John; Huizer-Pajkos, Aniko; McKenzie, Catriona; Phillips, Leo; Cogger, Victoria; Le Couteur, David; Jones, Brett; Hilmer, Sarah
Abstract : Background: A spectrum of histopathological changes have been described in isoniazid hepatotoxicity. The cause of increased isoniazid hepatotoxicity in old age is uncertain. Aims: To investigate the influence of age on histological and biochemical outcomes following a toxic regimen of isoniazid in male Fischer 344 rats. Methods: Young (6 months) and old (24 months) rats were fasted for 16 hours followed by a toxic regimen of isoniazid or saline vehicle (4 doses/day: 100, 75, 75, 75 mg/kg i.p. every 3 hours over 2 days). Fifteen hours after the last dose livers were prepared for histology and sera were collected for biochemical analysis. Results: Without reaching significance, the prevalence of necrosis was higher in young than old isoniazid treated animals (young 5/7, old 1/5; p  < 0.08). Compared to saline, steatosis was only more prevalent in old isoniazid treated animals (old: saline 1/9, isoniazid 4/5; p  < 0.05; young: saline 0/7, isoniazid 1/7; p  > 0.05) Again relative to saline, serum hepatotoxicity markers ALT and AST in isoniazid treated animals were unchanged or higher in young but unchanged or lower in old animals ( p  < 0.05). Amongst isoniazid treated animals, concentrations of toxic intermediates acetylhydrazine and hydrazine were higher in old than young animals ( p  < 0.05). Conclusion: Different patterns of injury to toxic doses of isoniazid were observed with age, with young rats showing a necroinflammatory pattern of injury, and old rats showing steatosis and higher levels of toxic intermediates.